(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
The contribution is interested in problems of volatile organic compounds emitted by wood shavings of different kinds of wood: pine (Pinus sylvestris) sapwood, (Pinus sylvestris) heartwood, English oak (Quercus robur), western red cedar (Thuja plicata) in the comparing of them. In the same time the olfactometric influence of individual components emitted by western red cedar and sapwood of pine was under review. In the work there is also described the relation among the results reported during the olfactometric measuring and the results re ported during the measuring of volatile organic compounds especially emitted by cedar wood. The dependence of Limonene and α Pinene olfactory activity on the concentration of organic compounds emitted by tested samples of wood with strong olfactory activity. The properties of odours of the above are judged by equipment Sniffer 9000. The amount of emission of VOC emitted by choice kind of woods is monitored in de pendence on time (72, 336 and 672 hours after planning wood shavings). The results are compared with sensory perceptions and the qualitative and quantitative analysis of VOCs performed by the help the gas chromatograph (Agilent 6890) with mass selective detector (MS 5973 Network) and short part thermal desorption (model TD-4).